1989
DOI: 10.1021/j100352a019
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical synthesis of disilane from silane with infrared laser radiation

Abstract: polymer has photophysical properties very similar to those of the parent complex and that the structure of the polymer must remain sufficiently open so that the accessibility to quenchers is not greatly reduced. While the charge on the polymer does affect the quenching by MV2+ and the back-reaction between the Ru(II1) center and MV", it is also apparent that interactions between the heteroaromatic moieties of the polymer and viologen quenchers also play a significant role. It is clear therefore that if the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent laboratory experiments investigated the photochemistry of silane and the subsequent reactions of the photodissociation products. These data suggested that more complex, hydrogenated silicon clusters of the generic formula Si 2 H x (x = 1-6) are formed in these processes (Cook et al 2001;Zavelovich & Lyman 1989;Hu et al 2003;Glenewinkel-Meyer et al 1993;Tonokura et al 1992;Perkins et al 1979;Borsella et al 1988;Ashfold et al 1996;Aka & Boch 2002;Wang & Huang 1998;Oikawa et al 1994). Their experiments suggest that a rich silane chemistry is expected in the circumstellar envelope of IRC+10216: photochemistry of silane molecules close to the photosphere could contribute to the formation of small hydrogenated silicon clusters of the generic formula Si 2 H x .…”
Section: Introductionmentioning
confidence: 96%
“…Recent laboratory experiments investigated the photochemistry of silane and the subsequent reactions of the photodissociation products. These data suggested that more complex, hydrogenated silicon clusters of the generic formula Si 2 H x (x = 1-6) are formed in these processes (Cook et al 2001;Zavelovich & Lyman 1989;Hu et al 2003;Glenewinkel-Meyer et al 1993;Tonokura et al 1992;Perkins et al 1979;Borsella et al 1988;Ashfold et al 1996;Aka & Boch 2002;Wang & Huang 1998;Oikawa et al 1994). Their experiments suggest that a rich silane chemistry is expected in the circumstellar envelope of IRC+10216: photochemistry of silane molecules close to the photosphere could contribute to the formation of small hydrogenated silicon clusters of the generic formula Si 2 H x .…”
Section: Introductionmentioning
confidence: 96%
“…In the literature SiH2 is discussed to be the active species in a-Si:H film formation [33-353. Reactions of SiH2 in the gas phase are possible, forming higher silanes (e. g. Si2H6) by insertion of the SiH2 into Si -H-bonds of undissociated SiH4 molecules [30,31,36]. In the present paper SiH4, Si2H6, and mixtures of both were used as reactant gases.…”
Section: Introductionmentioning
confidence: 99%